2019
DOI: 10.12657/denbio.081.010
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and habitat conditions of Pinus cembra forests in the Tatra Mountains

Abstract: Relic Pinus cembra forests were among the least studied plant communities in the Western Carpathians. Their distribution in this mountain range is limited only to the Tatras. The lack of comprehensive research on the Polish and Slovakian sides of the Tatras led to considerable discrepancy regarding their distribution (300-1170 ha) as well as habitat conditions. Their occurrence on limestones and in the Western Tatras was contested. Therefore, the aim of this work was to determine the distribution and habitat c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…of the alpine forest line in comparison to other (mittelgebirge) mountain ranges with native Norway spruce belt and simultaneously with Arolla pine absence (Plesník, 1971;Kučera, 2012a;Zięba et al, 2019), the respective high mountain mixed P. cembra woodlands could be labelled with the adjective "altimontane" (= occurring in the very high montane altitudes).8 In the Pyrenees the similar role is taken by high-altitude Pinus uncinata woodland (cf. Rivas-Martínez, 1968).…”
Section: A Note To Terminology Of the Picea Abies Altitudinal Vegetat...mentioning
confidence: 98%
See 2 more Smart Citations
“…of the alpine forest line in comparison to other (mittelgebirge) mountain ranges with native Norway spruce belt and simultaneously with Arolla pine absence (Plesník, 1971;Kučera, 2012a;Zięba et al, 2019), the respective high mountain mixed P. cembra woodlands could be labelled with the adjective "altimontane" (= occurring in the very high montane altitudes).8 In the Pyrenees the similar role is taken by high-altitude Pinus uncinata woodland (cf. Rivas-Martínez, 1968).…”
Section: A Note To Terminology Of the Picea Abies Altitudinal Vegetat...mentioning
confidence: 98%
“…the Tatra Mountains (equivalently to the Alps), whereby this species change has also considerable effect on the altitudinal rise of the upper forest line in comparison to the other Western Carpathian mountain ranges (Plesník, 1971); however, historical deforestation considerably reduced or destroyed native mixed Arolla pine forests, especially in their western (Západné Tatry Mts) or eastern part (Belianske Tatry Mts) (cf. Kučera (2019b, chapter 3.3), andZięba et al (2019), detailed distribution map in their el. appendix).6 6 As the last glacial mixed Pinus cembra woodland was present in the Podtatranská kotlina Basin lying between the Tatra Mountains and the Low Tatras as well as in other rather unexpected regions (Jankovská, 1984;Jankovská, 1991;Jankovská et al, 2002;Jankovská et al, 2018;Pokorný et al, 2015), it may be expected that Pinus cembra was a native tree of the lowest parts of Low Tatras' slopes during the more favourable periods of the Würm glaciation and after its ending the species probably survived the Atlantic period -similarly like within the Tatra Mountains -also in the uppermost elevations of the highest parts of the Low Tatras and on other ecologically extreme habitats, as for example rugged rocky terrain of some carbonate summits (Krakova hoľa Mt.…”
Section: General Upper Line Of Norway Spruce Altitudinal Vegetation Z...mentioning
confidence: 99%
See 1 more Smart Citation
“…The study site was located in the upper treeline ecotone in the Tatras (the Western Carpathian Mountains) (49 • 12 54.48 N; 20 • 4 34.68 E) (Figure 1). The Tatra Mountains, having classic alpine terrain and elevations of over 2600 m a.s.l., represent the highest and most rugged Carpathian mountain range [22,34]. The studied stone pines grow in high-elevation cliff forests on steep, granite slopes (ca.…”
Section: Study Area and Climatementioning
confidence: 99%
“…A low nutrient supply, as well as significant disruptions produced by gravity-rock and avalanche, snowfall and snow accumulation, and winds-contribute to the harsh environment of cliffs [17]. The Swiss stone pine (Pinus cembra L.) is a taxon with scattered populations (the Alps and Carpathian Mountains), exhibiting the finest adaptations for colonisation and growth in high-elevation cliffs [9,[20][21][22][23][24]. Previous studies from the Alps [9,[24][25][26] and Carpathian Mountains [20,27,28] have shown that the response of this species to climate changes is not stable over time.…”
Section: Introductionmentioning
confidence: 99%